Impact of Turmeric as Dietary approach on HER2 expression in blood of Gastric cancer Patients - Akhileshwar Kumar Srivastava; Divya Singh; Mallika Tewari; Hari Shankar Shukla; Bijoy Krishna Roy (International Journal of Phytomedicine, 2014)
Curcumin as an active ingredient of turmeric acts as repressor against proteins expressed in cancerous cell. However, due to poor absorption, little is known about the effect of curcumin on HER2 expression in blood. A blood samples were drawn from ten subjects of gastric cancer aged 37 to 80 years using turmeric as random doses in diet. For hypothesising of study, subjects were convinced to use a constant dose (500 mg) of turmeric twice in a day till the five days and then blood was drawn. Out of ten, three subjects had detectable curcumin, whereas in blood of nine subjects including three showed overexpression of HER2 status (>15 ng/ml) at random doses of turmeric. At constant dose (500 mg) of turmeric, six subjects out of ten had increasing curcumin level with decreasing HER2 status in blood, whereas in two subjects, HER2 status was remain unchanged due to no detection of curcumin. In other two subject underwent for chemotherapy had low HER2 status without curcumin detection. An inverse relation of curcumin holds on HER2 status in blood of four subjects with different body mass of same age group after taking constant doses of turmeric powder. The curcumin bioavailability in blood depending on higher doses of turmeric and physical status of subjects may inhibit the HER2 expression.